Pengecualian Rahasia Bank Bagi Kurator Melalui Putusan Pengadilan Niaga Berdasarkan Undang-Undang Nomor 4 Tahun 2023 - Abdul Aziz (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Bankruptcy is a situation where a debtor is unable to pay their debts to their creditors. If a debtor is declared bankrupt by a court, the administration of the bankrupt assets will be carried out by a curator. The purpose of bankruptcy is to pay the rights of creditors in a certain order. However, the task of the curator is not always easy because there are several obstacles such as uncooperative debtors or conflicting laws and regulations, such as bank secrecy regulated in the Banking Law and the Bankruptcy and PKPU Law. As an example, in Ryan Gunawan Lubis' thesis titled "Juridical Review of Curator's Duties in Handling Bankruptcy and Bank Secrecy," there is a case where a bank refused a request from the curator who had obtained a final and binding decision from the Commercial Court to maintain the confidentiality of its customers. However, with the enactment of the P2SK Law, based on Article 40A paragraph (1) letter c and Article 43A of the P2SK Law, curators are now considered part of the authorized parties to exempt bank secrecy based on a final and binding decision from the commercial court. Therefore, the law can provide protection for creditors to obtain their debts from the debtor.